Pendampingan Pengurusan Legalitas Usaha Sebagai Upaya Menjamin Keberlanjutan Usaha Mikro - Puspaningrum; Widiastuti (Fakultas Hukum Universitas Semarang, 2025)
The aims of this community service were assited and encouraged the micro-entrepreneurs who make and trade processed food to meet legality requirements, and ensure the sustainability of their business. This activity was based on the fact that there are many women as business actors, especially in the micro category, did not meet legal requirements. They thought legality process was difficult and expensive. However they had meet the legality of the business, and the legality of the product process and trade. The methods was carried out to achieve these aims had socialized the functions and benefits of business legality and product distribution, trained in making labels using the Canva application, processed of got business registration number or NIB and certificate of home industry food product or SPP-IRT. The results of these services activities shown the process for managing business legality actually simple and the partners should be themselves, but due to limited information, so must be trained and mentored. The training is carried out using the Canva application to create product labels, and assistance in processing NIB and PIRT at related agencies. The legality of business, products and product packaging labels provides protection for partners as business actors and guarantees the sustainability of their business Keyword: Legality Business;Business Registration Number; Certificate of Home Industry Food Product; Label of Food Product